IMPACT OF FAKE NEWS ON THE CREDIBILITY OF NATIONAL HINDI NEWS CHANNELS: A STUDY OF VIEWER PERCEPTIONS IN UTTARAKHAND - Kumar, Pawan Lalchand; Kulshreshtha, Ashish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the impact of fake news on the credibility of national Hindi news channels, focusing on viewer perceptions in Uttarakhand. As misinformation proliferates across media platforms, understanding its effects on audience trust and news consumption habits is crucial for maintaining an informed citizenry and a healthy media ecosystem.The research uses a survey methodology to examine viewers’ news consumption patterns, awareness and perception of fake news and the subsequent impact on channel credibility. Questions explore viewing frequency, preferred channels and perceived exposure to misinformation. The study assesses viewers’ confidence in identifying fake news and investigates which news categories are most susceptible to false information.Central to this investigation is how fake news affects trust in Hindi news channels. The survey measures changes in viewer trust levels and explores factors influencing news credibility judgments. It also examines whether fake news concerns have led viewers to abandon specific channels, providing insight into potential economic impacts on news organizations.The study also explores viewers’ perspectives on combating fake news, assessing the perceived importance of verifying news across multiple sources, interest in media literacy programs, and attitudes towards stricter regulations for news channels. By analyzing these aspects, the research aims to provide a comprehensive understanding of the fake news phenomenon in Hindi-language television news. The findings will offer valuable insights for news organizations, policymakers, and media literacy advocates, potentially informing strategies to enhance news credibility, combat misinformation, and restore viewer trust in an era of information overload and increasing media scepticism.